Risk of Venous Thromboembolism in Patients Nursed at Home or in Long-Term Care Residential Facilities - Guido Arpaia; Federico Ambrogi; Maristella Penza; Aladar Bruno Ianes; Alessandra Serras; Patrizia Boracchi; Claudio Cimminiello (International Journal of Vascular Medicine)
Background. This study investigated the prevalence of and impact of risk factors for deep venous thrombosis (DVT) in patients with chronic diseases, bedridden or with greatly limited mobility, cared for at home or in long-term residential facilities. Methods. We enrolled 221 chronically ill patients, all over 18 years old, markedly or totally immobile, at home or in long-term care facilities. They were screened at the bedside by simplified compression ultrasound. Results. The prevalence of asymptomatic proximal DVT was 18% (95% CI 13–24%); there were no cases of symptomatic DVT or pulmonary embolism. The best model with at most four risk factors included: previous VTE, time of onset of reduced mobility, long-term residential care as opposed to home care and causes of reduced mobility. The risk of DVT for patients with reduced mobility due to cognitive impairment was about half that of patients with cognitive impairment/dementia. Conclusions. This is a first estimate of the prevalence of DVT among bedridden or low-mobility patients. Some of the risk factors that came to light, such as home care as opposed to long-term residential care and cognitive deficit as causes of reduced mobility, are not among those usually observed in acutely ill patients.